Pemerintahan Digital dan Kepercayaan Publik: Analisis Bibliometrik dan Wawasan Kebijakan untuk Memperkuat Legitimasi Pemerintahan - Diva Nugraha; Dede Sri Kartini; Andi Kasman (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2026)
This bibliometric study identifies global research on digital governance and explores the policy implications for the digital transformation of government in Indonesia. The analysis was conducted using data from the Scopus database and the RStudio software (Biblioshiny). The findings reveal two main thematic clusters. The first cluster focuses on digital transformation and the socio-ministrative aspects of governance, with keywords such as digital governance, governance approaches, technology adoption, innovation, trust, and COVID-19. The second cluster highlights the technical and policy dimensions, withkeywords such as e-government, public policy, transparency, open data, decision making, and artificial intelligence. The connection between the two clusters through the e-government node reflects the interdisciplinary nature of digital governance research. These findings emphasize the importance of cross-country and cross-disciplinary academic collaboration in strengthening inclusive, data-driven, and citizen-oriented digital transformation strategies. Strengthening this collaboration is also intended to bolster the governance legitimacy that underpins public trust in digital services. In the Indonesian context, this study recommends strengthening the integration of national digital policies, enhancing institutional capacity, and developing an open research ecosystem to support adaptive and participatorydigital governance.